FACTORS THAT EFFECT TURNOVER INTENTION WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT FOOD AND BEVERAGES DISTRIBUTION COMPANIES IN BATAM - Delicia Olivian; Agustinus Setyawan (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
Nowadays workplace filled with Gen X and Y employee, it is stated that by 2025, the employment field will be filled by millennials. Human resources are an asset to a company, turnover intention emerge a big problem for company every year. This research will be aim to determine and analyze factors that affect turnover intention with job satisfaction as intervening variable. Questionnaires was distributed to 360 employee that work in food and beverages distribution companies in Batam. However, there is only 280 data that can be analyze due to incompleteness and some questionnaire that didn’t return. The data is examined with SPSS to analyze the descriptive data and Smart PLS program to examine the relationship between independent to dependent variables while intervening through an intervening variable. The result of this study shown that there is a direct effect from salary, transformational leadership and job satisfaction toward turnover intentions. It also shows that there is an indirect effect from salary and transformational leadership towards turnover intention while it is mediating through job satisfaction. In other hand, it was found that work stress, emotional intelligence is not significant in giving effect towards turnover intention with or without the intervening from job satisfaction.